Foundations and Applications for Contractualist Business Ethics - Heugens, Pursey P. M. A. R. (Journal of business ethics, 2006)
Contractualism is one of the most promising ‘centers of gravity’ in business ethics. In this guest editorial we provide a concise roadmap to the field, sketching contractualism’s historic and disciplinary antecedents, the basic argumentative structure of the contract model, and its boundary conditions. We also sketch two main dimensions along which contributions to the contractualist tradition can be positioned. The first dimension entails positive versus normative theorizing – does a given contribution analyze the world as it is or how it ought to be? The second dimension involves four different levels of analysis that are commonly employed in contractualist business ethics: the nano, micro, meso, and macro levels. We then proceed to position the articles comprising this special issue along these two dimensions.